Prevalence of Prenatal Depression Among Pregnant Women and the Importance of Resilience: A Multi-Site Questionnaire-Based Survey in Mainland China - Zhang, Lijuan; Yang, Xiaoshi; Zhao, Jinfeng; Zhang, Weiyu; Cui, Can; Yang, Fengzhi; Ma, Ruqing; Jia, Yajing (Frontiers in Psychiatry, 2020)
Background: Prenatal depression is associated with adverse maternal and fetal health consequences, yet it has not raised sufficient concerns in China. Psychological worries and stress may lead to prenatal depression, but resilience could relieve some of the negative effects of worries and stress and mitigate prenatal depression. Aims: This study aimed to assess the prevalence of prenatal depression and explore its associated factors. Method: A multisite cross-sectional study was conducted that included 605 pregnant women from three hospitals in two provincial capitals (Shenyang and Zhengzhou) and one municipality (Chongqing). A smartphone questionnaire was employed to assess prenatal depression using the Center for Epidemiologic Studies Depression Scale (CES-D). Multivariate logistic regression analysis was performed to explore factors associated with prenatal depression. Results: The prevalence of prenatal depression (CES-D≥16) among Chinese pregnant women was 28.4%. Logistic regression analyses revealed that prenatal depression was positively associated with worries about appearance (odds ratio [OR] 1.666, 95% confidence interval [CI] 1.043-2.661) and perceived stress (OR 1.156, 95% CI 1.104-1.211) and negatively associated with monthly income, relationship with mother (OR 0.287, 95% CI 0.103-0.796), and resilience (OR 0.935, 95% CI 0.918-0.953). Conclusion: These findings revealed that Chinese pregnant women suffered from high levels of prenatal depression (28.4%). Worries about appearance and perceived stress were risk factors for prenatal depression, whereas a pregnant woman’s harmonious relationship with her own mother and resilience could relieve the negative impacts of pregnancy that can lead to prenatal depression. Improving resilience and maintaining harmonious relationships with mothers should be emphasized in order to reduce the detrimental effects of pregnancy and improve the mental well-being of pregnant women.